A methodology for determining the evolution law of gob permeability and its distributions in longwall coal mines. (16th March 2016) - Zhang, Cun; Tu, Shihao; Zhang, Lei; Bai, Qingsheng; Yuan, Yong; Wang, Fangtian
Abstract: In order to understand the permeability evolution law of the gob by mining disturbances and obtain the permeability distribution of the fully compacted gob, comprehensive methods including theoretical analyses of monitoring data and numerical simulation are used to determine the permeability of gobs in the mining process. Based on current research, three zones of the vertical stress and permeability in the gob are introduced in this article, which are the caving rock mass accumulation zone, the gradually compacted zone and the fully compacted zone. A simple algorithm is written by using FISH language to be imported into the reservoir model. FISH language is an internal programming language in FLAC3D. It is possible to calculate the permeability at each zone with this algorithm in the mining process. Besides, we analyze the gas flow rates from seven gob gas ventholes (GGV) located on a longwall face operated in a mine of a Huainan coalfield in Huainan City, China. Combined with Darcy's law, a calculation model of permeability around GGV in the gob is proposed. Using this model, the evolution law of permeability in the gob is deduced; the phases of permeability evolution are the decline stage and the stable stage. The result of the vertical stress monitoring data and good fitting effect of the permeability to the experimental data show that the permeability decline caused by the compaction of the gob is the principal reason for the decline stage. The stable stage indicates that the gob has been fully compacted, and the average period of full gob compaction is 47.75 d. The permeability in the middle of the compacted gob is much smaller than the permeability on the edge of the gob which presents an O shape trend. Besides, the little difference among the results of the numerical simulation, the permeability calculation model and other commonly used calculation models validate the correctness of the permeability calculation model and numerical simulation results.